2017
DOI: 10.1556/030.64.2017.017
|View full text |Cite
|
Sign up to set email alerts
|

Colistin resistance associated with outer membrane protein change in Klebsiella pneumoniae and Enterobacter asburiae

Abstract: In this study, outer membrane proteins (OMPs) of colistin-resistant Klebsiella pneumoniae and Enterobacter asburiae were analyzed. One colistin-susceptible and three colistin-resistant K. pneumoniae sequence type 258 strains as well as one colistin-susceptible E. asburiae and its colistin-heteroresistant counterpart strain were involved in the study. OMP analysis of each strain was performed by microchip method. Matrix-assisted laser desorption ionization time of flight/mass spectrometry (MALDI-TOF/MS) investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Other efflux pumps, including KpnEF, along with alterations in the LPS and outer membrane proteins mediated by changes in the ramA and omp genes have also been reported to decrease susceptibility to colistin ( Srinivasan and Rajamohan, 2013 ; De Majumdar et al, 2015 ; Kádár et al, 2017 ). However, we found no mutations in KpnEF in our strains.…”
Section: Resultsmentioning
confidence: 99%
“…Other efflux pumps, including KpnEF, along with alterations in the LPS and outer membrane proteins mediated by changes in the ramA and omp genes have also been reported to decrease susceptibility to colistin ( Srinivasan and Rajamohan, 2013 ; De Majumdar et al, 2015 ; Kádár et al, 2017 ). However, we found no mutations in KpnEF in our strains.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, resistance to colistin is also attributed to change in porin profile among Enterobacteriaceae [39]. All the isolates showed similar pattern of porins, loss of OmpK35 but intact OmpK36.…”
Section: Analysis Of Colistin Resistancementioning
confidence: 92%
“…Furthermore, OmpC and OmpW were detected in the colistin-susceptible E. asburiae , whereas OmpA and OmpX were identified in the colistin-resistant counterpart. This demonstrated that the altered Gram-negative cell wall may contribute to acquired colistin resistance in Enterobacteriaceae [ 119 ]. Another study investigated the influence of lipid A acylation pattern on the crucial interaction between the LPS of a clinical K. pneumoniae isolate and polymyxins.…”
Section: Bacterial Resistance To Polymyxins and Changes In Membranmentioning
confidence: 99%